The Competence and Authority of Midwives in giving Birth without the assistance of a Doctor in Nigeria - Aidonojie, Paul Atagamen; Aidonojie, Esther Chetachukwu; Afolabi, Majekodunmi Toyin; Eregbuonye, Obieshi; Adebayo, Adesoji Kolawole (Jambura Law Review, 2024)
Life per se is not short, but our actions and inaction often result in the shortness of our life. This quote is concerning the fact that in Nigeria and the global standard it is required that during childbirth delivery there should always be a doctor present to avoid complications that may result in the death of the mother or the child. However, in Nigeria, it has been observed that the majority of the childbirth delivery conducted in hospitals or at any other place by local or trained mid-wife are often executed without the involvement or presence of a doctor.  In this regard, is it legally and medically in abeyance to conduct childbirth delivery without the aid of a doctor, given the possible complication that may result in loss of life and damage to the mother and child. It is in this regard that this study tends to adopt a hybrid method of study (involving a doctrinal and non-doctrinal) in ascertaining the legal issues and challenges in curtailing mid-wife involvement in child delivery in the absence of a medical doctor. 307 questionnaires were distributed to respondents, and the data obtained were analyzed by adopting an analytical and descriptive method. The study, therefore, found that there are very high incidences of the mortality rate of a pregnant mother and their baby during delivery by mid-wife and nurses given the absence of a doctor. The study further found that though there are laws and ethical codes that regulate childbirth delivery in Nigeria, however, there are challenges that often mitigate the curtailment of mid-wife or nurses involved in childbirth delivery without the aid of a doctor. We thus concluded and recommended that authorities should establish effective regulations and sanctions for midwives or nurses participating in childbirth deliveries without the presence of a doctor.